1999
DOI: 10.1590/s0100-879x1999000800007
|View full text |Cite
|
Sign up to set email alerts
|

Ethological analysis of mother-pup interactions and other behavioral reactions in rats: effects of malnutrition and tactile stimulation of the pups

Abstract: Mother-pup interaction, as well as other behavioral reactions were studied during the lactation period in 24 litters of Wistar rats and their dams fed either a 16% (control -C; 12 litters) or a 6% (malnourished -M; 12 litters) protein diet. The diets were isocaloric. Throughout lactation there was a 36.4% weight loss of M dams and a 63% body weight deficit in the M pups when compared to control pups. During this period, half of the litters were exposed daily to additional tactile stimulation (CS or MS), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
12
0
9
Order By: Relevance
“…Protein or protein-calorie malnutrition imposed during lactation changes the quantity and quality of mother-pup interactions and may lead to long-lasting adverse effects on the behavior of rats in the adult life [4042]. Reported data have been shown that malnourished mothers spend more time in the nest [41], take longer to gather the pups in the pup retrieval test [40] and change the eating pattern [43].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein or protein-calorie malnutrition imposed during lactation changes the quantity and quality of mother-pup interactions and may lead to long-lasting adverse effects on the behavior of rats in the adult life [4042]. Reported data have been shown that malnourished mothers spend more time in the nest [41], take longer to gather the pups in the pup retrieval test [40] and change the eating pattern [43].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Reported data have been shown that malnourished mothers spend more time in the nest [41], take longer to gather the pups in the pup retrieval test [40] and change the eating pattern [43]. Like the mothers, the malnourished pups also presented changes in the behavior as compared to well-nourished pups, mainly by expressing more time in the nest, less time exploring the environment, less time separated in groups and more time in ultrasonic calls [42,44]. …”
Section: Animal Studiesmentioning
confidence: 99%
“…A multitude of animal studies have delved into the effects of prenatal PEM during gestation and postnatal PEM on behavioral abnormalities in the adult progeny [92, 110]. The protein malnourished rat pups subjected to prenatal and postnatal PEM exhibit greater nesting period and passive [5] but lesser locomotor and exploratory behavior [111] during the preadolescent period while exhibiting aggressive and dominance behavior traits in adulthood [112]. Prenatal and postnatal PEM is also associated with deficits in spatial learning and memory in adult rats despite allowing nutritional recovery [113].…”
Section: Discussionmentioning
confidence: 99%
“…Esta perda de peso das mães desnutridas pode ser atribuída a um maior gasto energético na amamentação e nos cuidados com os filhotes sem a ingestão correspondente (DE OLIVEIRA, 1985). Alguns estudos mostram que as mães desnutridas passam mais tempo amamentando e menos tempo descansando fora do ninho do que as mães controle (LEVITSKY et al, 1975;RIUL et al, 1999), levando a um maior consumo de energia nesses animais. Outros revelaram que ratas lactantes que recebem dieta com Discussão ________________________________________________________________________________________ deficiência de proteína tendem a consumir menor quantidade de alimento (LIMA et al, 1993;CAMBRAIA et al, 1997;RIUL et al, 1999).…”
Section: Discussionunclassified